Field Comparison of DNA‐Labeled Nanoparticle and Solute Tracer Transport in a Fractured Crystalline Rock. Issue 8 (6th August 2019) - Kittilä, A.; Jalali, M. R.; Evans, K. F.; Willmann, M.; Saar, M. O.; Kong, X.‐Z.
Abstract: Field tracer experiments were conducted to examine tracer transport properties in a fracture‐dominated crystalline rock mass at the Grimsel Test Site, Switzerland. In the experiments reported here, both the DNA nanotracers and solute dye tracers were simultaneously injected. We compare the transport of DNA nanotracers to solute dye tracers by performing temporal moment analysis on the recorded tracer breakthrough curves and estimate the swept volumes and flow geometries. The DNA nanotracers, approximately 166 nm in diameter, are observed to travel at a higher average velocity than the solutes but with lower mass recoveries, lower swept volumes, and less dispersion. Moreover, size exclusion and potentially, particle density effects are observed during the transport of the DNA nanotracers. Compared to solute tracers, the greatest strength of DNA nanotracers is the demonstrated zero signal interference of background noise during repeat or multitracer tests. This work provides encouraging results in advancing the use of DNA nanotracers in hydrogeological applications, for example, during contaminant transport investigations or geothermal reservoir characterization. Key Points: DNA‐labeled nanotracer transport is evaluated on a first field demonstration in crystalline rock Heterogeneity of flow field and size exclusion strongly influences DNA nanotracer response curves DNA nanotracer is highly suitable for tracer tomography and tracing particulate‐bound contaminant transport